(untitled) (PUBMET, 2022)
We believe that when publishing a journal, no matter if it is a new or an already existing one, a modern, full-featured editorial management and publishing platform is a must. Streamlined editorial processes are a key to the success of a scholarly journal, however, they should also be enjoyable for its editors, authors, reviewers and readers. At ARPHA Platform, we make sure that editorial work remains hassle-free and time-efficient for all journal users. ARPHA’s mission is to let journal editors focus on the scientific content, rather than time-demanding tasks, e.g. tracking manuscript turnaround, following up delayed revisions, moving data between different platforms, or disseminating content in both human- and machine-readable ways. ARPHA is a full-featured open access publishing platform for journals, books and data, with provision of managed hosting services. Several other services (website design and setup, production, semantic markup, distribution, archiving, indexing, promotion, journal management and more) are available on demand. Offered as Software as a Service (SaaS), ARPHA allows users to build their own publishing solution to manage and host journals, books, conference abstracts, proceedings and institutional documents. Want to learn more about how it works and how to move your journal to ARPHA? Join our workshop!